(untitled) (Global Journal of Medical Research, 2023)
Background The patients affected with COVID-19 present with a variety of oral manifestations In this context our systematic review was conducted to summarize the findings regarding oral manifestations of COVID-19 Methods An extensive literature search of several electronic bibliographic databases PubMed Scopus Science direct Litcovid was done to retrieve all articles published in the English language from January 1 2020 to June 30 2022 reporting the prevalence of oral manifestations among COVID-19 individuals